From planetary emergency to regenerative economies - Accounting for nature in measures of sustainable development - Jana Stoever; Andre Reichel (Forum for a New Economy, 2022)
Starting from a world in which resources have become scarce and planetary boundaries have been reached or exceeded, the paper discusses how these changes affect our understanding of (economic) progress and sustainable development. In doing so, the paper addresses three important points in the discussion on sustainability. Firstly, the question of "means" and "ends", secondly, the visualization of this reality in the measurement of sustainable development, taking into account the specific characteristics of the environment/nature, and thirdly, the question of whether a concept that maps "regenerative development" could be suitable to account for the current state of natural systemsthat have already exceeded their (planetary) limits.
Keywords: Q01; Q2; Q3; Q5; 330; Sustainable development; planetary boundaries; well-being; wealth; means and ends; social and economic progress; conservation & restoration; regeneration